Kilns in East and North Asia The adoption of ceramic industries - Nagatomo, Tomoko; Shinoto, Maria; Nakamura, Daisuke (BAR International, 2022)
The start of ceramic industry is an important stage in mass production and is closely related to social complexity and social exchanges including the immigration of specialists. The introduction of high-temperature operations and varying firing regimes is a technological breakthrough in ceramic production. This book discusses the introduction and the background of kilns and advanced technology in the wider area of East Asia, covering the early appearances of the typical East Asian kiln technology in China, and its distribution to the Russian Far East, the Korean peninsula, and the central Japanese archipelago. Using both scientific and archaeological analysis, this book tries to help better understand the introduction factors of kilns, management of kilns by each regime, and the development of technology. An extensive glossary at the end of the book orientates readers not familiar with research in East Asia or languages referenced in this book.